2007
DOI: 10.1007/s11295-007-0095-z
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to Plum pox virus in apricot (Prunus armeniaca L.)

Abstract: The inheritance of resistance to Plum pox virus (PPV) has been studied in 1,178 apricot hybrids. Seven hundred and eighteen F1 hybrids, obtained from controlled crosses between the susceptible Greek cultivar "Bebecou" and the resistant PPV cultivars of American origin ("Stark Early Orange," 'NJA2," 'Veecot," "Sunglo," "Harlayne," and "Orangered") were evaluated for resistance to the PPV-M (Marcus) strain, 8 years after artificial inoculation. The inheritance of resistance to PPV has been additionally studied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…This is most likely due to scoring of the resistant genotype. Several studies suggest that the resistance is conferred by a limited number (1-3) of genes (Dicenta et al 2000;Dosba et al 1992;Krška et al 2002;Karayiannis et al 2007;Soriano et al 2007). Nevertheless, in spite of progress in understanding inheritance of PPV resistance, the unknown pedigree of North American cultivars hampers exploitation of the genetic resources of resistance within apricot germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…This is most likely due to scoring of the resistant genotype. Several studies suggest that the resistance is conferred by a limited number (1-3) of genes (Dicenta et al 2000;Dosba et al 1992;Krška et al 2002;Karayiannis et al 2007;Soriano et al 2007). Nevertheless, in spite of progress in understanding inheritance of PPV resistance, the unknown pedigree of North American cultivars hampers exploitation of the genetic resources of resistance within apricot germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery in a case of progeny derived from 'Stark Early Orange' x 'Bebecou' has been described by Karayiannis et al (2008) who suggested that 'resistance inherited from parent cv. ''Stark Early Orange'' is not ''hypersensitivityrelated'' or ''immunity'' type, but a ''recovery'' from infection'.…”
Section: Resultsmentioning
confidence: 99%
“…The theory of at least three genes involved was also expressed (Guillet-Bellanger & Audergon 2001;Salava et al 2005). The monogenic hypothesis of resistance fitted better to the observed data (Dicenta et al 2000;Lambert et al 2007;Rubio et al 2007;Karayiannis et al 2008;Soriano et al 2008).…”
Section: Introductionmentioning
confidence: 82%
“…Badenes et al were the first to suggest the role of Eastern Asiatic species, particularly P. mandshurica, as a potential source of PPV resistance into North American germ-plasm [32]. The results from Karayiannis et al [31,33] gave more support to this idea, even if not all the progenies of P. mandshurica were PPV resistant [34]. North American selections derived from P. mandshurica were introduced for their cold hardiness in midwinter and spring, late blooming and the ability to set fruit under adverse conditions for pollination [35].…”
Section: Kostina Et Al Compared the Inheritance Of Dormancy Length Imentioning
confidence: 99%